The influence of the education on lifestyle’s modification among patients with hypertension and people with prehypertension - Zajchowska, Janina; Guty, Edyta; Dominik, Anna; Kozimala, Magdalena; Bilińska, Anna (Journal of Education, Health and Sport, 2018)
Introdution: The most frequent reason of non-efficient hypertension treatment is lack of cooperation between the patient and the doctor. Increasing the patient’s awareness is an important factor which can change the situation. We can do it with the help of educational programs. Purpose of work was to assess the effectiveness of education on the use of lifestyle modifications people with hypertension and prehypertension. Material and methods: The research covered 210 people with hypertension and prehypertension. There were three stages of the research. First stage of the research contained determination of health activities in terms of hypertension. Second stage of the research: education – three patients meetings in small groups twice a week (each meeting lasted an hour and a half). The third stage of the research was conducted three months after the education program. Then, the health activities in terms of hypertension were determined once again. Results: The education have influence some healthy activities in a positive way. After the education 86.2% people used methods which decrease arterial blood pressure. After the education the groups used mainly three methods which decrease arterial blood pressure: salt reduction (55.7%), regular physical activity (65.7%) and animal fat reduction in the diet (38.6%). Discussion: results were similar to results of antother scientific researchs in Poland (among others WOBASZ I, POLSCREEN) and other countries. Conclusions: The education carried out positively influenced some of the health behaviors of the respondents. The most popular methods non-pharmacological main methods for lowering blood pressure after education were salt reduction, regular physical activity and reduced animal fat content diet. The best effects of the educational program were observed among respondents with beginning hypertension.